Padma Aranya: Integrasi Wisata Wellnes Berbasis Alam Di Kebun Raya Bedugul - Suarmana, Restu (Jurnal Kajian Pariwisata Dan Perhotelan, 2025)
The Bedugul Botanical Garden in Bali holds great potential to be developed as a wellness tourism destination that integrates nature, spirituality, and local culture. This study proposes the concept of Padma Aranya, or Lotus Forest, a reflective tourism model centered around a natural lotus pond as a space for contemplation and inner healing. Using a descriptive qualitative method based on literature studies and secondary data, this research highlights the role of natural elements—such as forests, water, and silence—in reducing stress and supporting mental and spiritual well-being. Beyond offering a peaceful experience, this concept enhances the appeal of Bedugul, extends tourist stays, and strengthens Bali’s identity as a center for spiritual tourism. Rooted in the local wisdom of Tri Hita Karana and involving local communities, Padma Aranya is expected to become a sustainable model of silent tourism that fosters meaningful personal experiences while contributing to ecological, cultural, and economic preservation.